Ultraviolet light exposure, skin cancer risk and vitamin D production - RIVAS, MIGUEL (Oncol Lett, 2015)
The danger of overexposure to solar ultraviolet radiation has been widely reviewed since the 1980s due to the depletion of the ozone layer. However, the benefits of mild exposure of the skin to ultraviolet (UV) light have not been widely investigated. Numerous reports have demonstrated that an association exists between low light exposure to the sun, non-melanoma skin cancer and a lack of vitamin D synthesis. As vitamin D synthesis in the body depends on skin exposure to UVB radiation from the sun (wavelength, 290–320 nm), experimental measurements for this type of solar radiation are important. The present study analyzed data obtained from a laboratory investigating UV radiation from the sun at the University of Tarapacá (Arica, Chile), where systematic experimental UVB measurements had been performed using a calibrated biometer instrument since 2006. These data were compared with skin cancer data from the local population. The results demonstrated that the incidence of skin cancer systematically increased from 7.4 to 18.7 in men and from 10.0 to 21.7 in women between 2000 and 2006 in Arica, respectively; this increase may be due to multiple factors, including the lack of adequate levels of vitamin D in risk groups such as post-menopausal women and senior age. This marked increase may also be due to the high levels of UV radiation measured in this region throughout the year. However, it is not certain that the local population has adequate vitamin D levels, nor that their skin has been predominantly exposed to artificial light that does not allow adequate vitamin D synthesis. Thus, the current study presents the association between skin type IV, the time to induce solar erythema and the time required to produce 1,000 international units of vitamin D.